District Heating Systems in Republic of Moldova: Reality and Perspectives - Leu V.; Cernei M. (Problems of the Regional Energetics)
The article presents the history of centralised distric0.t heating systems in Republic of Moldova, evolution, current state and prospects for short-term investments financed by raising funds from external creditors. Centralized heating in the Republic of Moldova is analyzed in the light of the activities of the license holders, regulated by the National Energy Regulatory Agency, particularly of those from mun. Chisinau and mun. Balti. In most cases, this centralized heating supply systems are in operation over 50 years already, so their rehabilitation is very appropriate considering their over dated lifetime period, and the moral and physical wear. At the level of heat sources, the physical wear of the fixed assets is about 70%. The heat transportation and distribution networks are being now renovated, using pre-insulated pipes from expanded polyurethane, at the level of 10%, and the growth of the renovated pipes share will lead to the lowering of the energy losses in this systems. The scope of the paper is the analysis of the key technical indicators and the description of the experience regarding the projects related to the enhancement of energy efficiency of centralized heating systems in mun. Chișinau and mun. Bălți, projects that are carried out in the last years, and implemented with the financial support of the foreign partners. Are analyzed main functioning indicators of the centralized heating systems for the period 2015-2018 years, inclusive production volumes, supply, and level of heat losses. A short analysis regarding centralized heating in some European Union countries, has been presented, as well.